Analisis Kesalahan Manusia Pada Pengemudi Bus Rapid Transit (BRT) Menggunakan Metode Human Error Assessment And Reduction Technique (HEART) dan Systematic Human Error Reduction And Prediction (Studi Kasus : Brt Koridor I, Trans Semarang) - Eli Mas'idah; Akhmad Syakhroni; Annisa Ayu Rachmawati (OPSI, 2019)
Based on Trans Semarang Bus Rapid Transit (BRT) traffic accident data, it is known that the Trans Semarang BRT still often experiences traffic accidents. Corridor I Trans Semarang with the Mangkang-Penggaron route service area is the Corridor with the highest accident rate compared to other corridors. The high number of accidents occurs because of human error. To solve these problems, in this study using the HEART and SHERPA methods. The HEART method is used to find out what activities constitute critical activities that have the potential to cause accidents and also the probability of human error for each critical activity. Then the SHERPA method is used to strengthen the answers of the HEART method and also to determine recommendations for improvement to fix the existing problem. After conducting research and data processing using the HEART and SHERPA methods, it is known that sub-task 6.4 be careful when driving is a sub-task with the highest probability of human error is 0.549. Furthermore, the subtask was given recommendations for improvement in the form of zero accident socialization to all BRT Corridor I Trans Semarang drivers and to make a particular lane for BRT, especially Corridor I so that the road is separated from other private or public vehicles.